PENGGUNAAN METODE LOGIKA FUZZY SUGENO DALAM MENENTUKAN STATUS GIZI PADA BALITA - Muljono Muljono Muljono (Semantik, 2011)
Nutritional status of children is an important thing to be known by every parent. The need for more attention in the development of under-fives is based on the fact that malnutrition occurs in the present difficulty will not rule out the possibility of recovery. Toddlers included in the nutrition of vulnerable groups of society, namely the group most easily suffer from nutritional disorders. Reference standard in the nutritional status of children under five are generally weight, height, and age. Sugeno Fuzzy logic is one of the methods widely used in calculations to determine the decision. With the method can be carried out calculations in the determination of nutrition in infants with a precise, fast and accurate with the help of a computer for data processing.Keywords : Nutrient Definition, Fuzzy Logic, Sugeno, Fuzzy Variabel, Fuzzy Set